2014
DOI: 10.4103/1658-354x.130683
|View full text |Cite
|
Sign up to set email alerts
|

Addition of dexmedetomidine to bupivacaine in transversus abdominis plane block potentiates post-operative pain relief among abdominal hysterectomy patients: A prospective randomized controlled trial

Abstract: Background:Dexmedetomidine is an alpha 2 adrenergic agonist, prolongs analgesia when used in neuraxial and peripheral nerve blocks. We studied the effect of addition of dexmedetomidine to bupivacaine to perform transversus abdominis plane (TAP) block.Materials and Methods:A total of 50 patients scheduled for abdominal hysterectomy were divided into two equal groups in a randomized double-blinded way. Group B patients (n = 25) received TAP block with 20 ml of 0.25% bupivacaine and 2 ml of normal saline while Gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(46 citation statements)
references
References 26 publications
2
43
0
1
Order By: Relevance
“…41 Some scholars reported that 0.5 μg/kg dexmedetomidine with 0.25% bupivacaine for transversus abdominis plane block in 50 patients undergoing abdominal hysterectomy led to better local anesthesia and better pain control postoperatively without any major side effects. 42 In a double-blinded study, 60 adults undergoing thyroid surgeries received bilateral superficial cervical plexus block with the addition of 0.5 μg/kg dexmedetomidine to 0.5% ropivacaine, and exhibited a significantly prolonged and better quality of postoperative analgesia and patient satisfaction. 43 …”
Section: Effect Of Intraoperative Dexmedetomidine On Perioperative Pamentioning
confidence: 99%
“…41 Some scholars reported that 0.5 μg/kg dexmedetomidine with 0.25% bupivacaine for transversus abdominis plane block in 50 patients undergoing abdominal hysterectomy led to better local anesthesia and better pain control postoperatively without any major side effects. 42 In a double-blinded study, 60 adults undergoing thyroid surgeries received bilateral superficial cervical plexus block with the addition of 0.5 μg/kg dexmedetomidine to 0.5% ropivacaine, and exhibited a significantly prolonged and better quality of postoperative analgesia and patient satisfaction. 43 …”
Section: Effect Of Intraoperative Dexmedetomidine On Perioperative Pamentioning
confidence: 99%
“…Dexmedetomidine (DEX) is a highly selective α 2 -adrenergic agonist with a receptor affinity greater than clonidine, which acts through various mechanisms, such as increased hyperpolarization of action potential, causing hypnotic and analgesic effects [10]. Adding DEX as an adjuvant to bupivacaine has proven effectiveness for postoperative pain relief in various procedures such as cesarean section [11], abdominal hysterectomy [12], and knee arthroplasty [13]. Even a combination of DEX with bupivacaine has been proposed to be superior to bupivacaine alone or with tramadol in cholecystectomy procedures [14].…”
mentioning
confidence: 99%
“…Regarding the number of rescue analgesics in TAP block,[ 8 ] maximum number of demand boluses were observed between 4 and 24 h with plain bupivacaine, while our study shows maximum demands between 6 and 12 h. One reason for initial discrepancy can be the difference in anaesthesia technique that is general anaesthesia versus SAB (present study). The bupivacaine group required rescue analgesic from 4 to 12 h and magnesium group demanded rescue analgesic after 12 h postoperatively indicating shorter pain-free period and more requirement of analgesia in the bupivacaine group.…”
Section: Discussionmentioning
confidence: 49%